Association between diet protein score comprising plants to animal protein ratio and body composition in an Iranian population - Manoochehr Amin Amlashi; Amirhosein Jafarpour; Marzieh Hafezi Eirdmousa; Reza Homayounfar; Mojtaba Farjam; Alireza Askari (Scientific Reports)
Abstract Obesity is increasingly recognized as a leading cause of death and is associated with various comorbidities. This study evaluates the relationship between protein score, characterized by the plant-to-animal protein ratio (PAR) and total protein per calorie (Pro%), and body composition: fat percentage (FATP), fat mass (FATM), and fat-free mass (FFM). We categorized 4512 individuals (55.2% female) into tertiles based on their protein score and its components. Male participants in the highest and middle protein score tertiles exhibited significantly greater FFM in both adjusted and crude models, and lower FATP and FATM in adjusted model 2. FFM was elevated in the top (P < 0.001) and middle (P = 0.002) Pro% tertiles in males in both adjusted models and only in the top tertile of all models in females (P = 0.003). The analysis of male participants revealed significantly lower FATP and FATM in the highest tertiles of Pro% in adjusted models. Among female participants, only the highest PAR tertile was associated with significantly lower FATM in adjusted model 1 (P = 0.042). Our findings indicate that protein score and its components are associated with favorable body composition differences. Health administrators may leverage these insights to refine dietary guidelines.